Hydrogen saturation influence on erosion behavior of thin W-films under steady state nitrogen plasma impact - Glazunov, G.P.; Andreev, A.A.; Baron, D.I.; Volkov, E.D.; Hassanein, A.; Kitaevskiy, K.M.; Konotopskiy, A.L.; Lapshin, V.I.; Neklyudov, I.M.; Patokin, A.P. (Вопросы атомной науки и техники, 2005)
The erosion behavior of W-Pd bimetallic system was examined for both hydrogen saturated and non-saturated states under impact of steady state nitrogen plasma of a mirror Penning discharge. Possible physical mechanism is discussed to explain the essential decrease of erosion rate and damages of such systems (form change, macro-blistering and macro-flaking) caused by hydrogen saturation to high concentration. Досліджувалося ерозійне поводження W-Pd біметалічних систем у насиченому воднем стані і ненасиченому, при впливі стаціонарної азотної плазми відбивного розряду Пеннінга. Обговорюються можливі фізичні механізми, що пояснюють істотне зниження швидкості ерозії й ушкодження таких систем (зміна форми, макро- блістерінг і макро-флекінг), обумовлених насиченням воднем до високих концентрацій. Исследовалось эрозионное поведение W-Pd биметаллических систем в насыщенном водородом состоянии и ненасыщенном, при воздействии стационарной азотной плазмы отражательного разряда Пеннинга. Обсуждаются возможные физические механизмы, объясняющие существенное снижение скорости эрозии и повреждения таких систем (изменение формы, макро-блистеринг и макро-флэкинг), обусловленных насыщением водородом до высоких концентраций.